Plasmodium sporozoite biology - Frischknecht, Friedrich; Matuschewski, Kai (Cold Spring Harbor perspectives in medicine, 2017)
Plasmodium sporozoite transmission is a critical population bottleneck in parasite life-cycle progression and, hence, a target for prophylactic drugs and vaccines. The recent progress of a candidate antisporozoite subunit vaccine formulation to licensure highlights the importance of sporozoite transmission intervention in the malaria control portfolio. Sporozoites colonize mosquito salivary glands, migrate through the skin, penetrate blood vessels, breach the liver sinusoid, and invade hepatocytes. Understanding the molecular and cellular mechanisms that mediate the remarkable sporozoite journey in the invertebrate vector and the vertebrate host can inform evidence-based next-generation drug development programs and immune intervention strategies.
Gesehen am 11.05.2018